Ultimate peculiarity in angular spectrum enhances the parametric solution of the inverse Mie problem. (September 2019) - Konokhova, Anastasiya I.; Yastrebova, Ekaterina S.; Strokotov, Dmitry I.; Chernyshev, Andrei V.; Karpenko, Andrei A.; Maltsev, Valeri P.
Highlights: Ultimate peculiarity in the angular spectrum relates to the maximal dimension of a sphere. Sub-micron spheres become available for real-time characterization in a flow. Simplest solution of Mie inversion is applicable from biospheres to polymer beads. Abstract: With this study, we are introducing a new parameter, ultimate spectral peculiarity Lu, to be used in solution of the inverse Mie problem. This parameter is evaluated from a power spectrum of an angle-resolved light-scattering profile (LSP). Direct correlation of single sphere size and Lu allows sizing a homogeneous sphere from 0.6 µm. In order to determine the refractive index (RI) of the sphere we utilized the integral of the LSP within the particular angular range providing the largest uniqueness domain where both size and RI can be unambiguously determined. The integral and Lu were used in the spectral solution of the inverse Mie problem providing the real-time analysis of milk fat globules, spherized red blood cells, polymer and silica beads with the scanning flow cytometer.